The social media MBA your competitive edge in social media strategy development & delivery - Holloman, Christer; Adeyeri, Eb. (Chichester, West Sussex, U.K. Hoboken, N.J. Wiley, 2012)
"It's a fact that companies so far have only scratched the surface of what can be achieved with social media. Whatever continent, industry, company size, current degree of social media adoption or your job title, the purpose of this book is to inspire you to see how you can raise the bar further to reap new rewards. It will give you the tools to make a difference to your organisation's social media strategy development and delivery going forward. In addition it will also give you more intellectual support and confidence to discuss social media on a higher level with peers, inspire colleagues or negotiate and create support for increased investments from your leadership team. In The Social Media MBA editor Christer Holloman has crowd sourced 15 thought leaders from 4 continents to offer an exceptional educational programme written for experienced social media professionals just like you. In addition, learn through cases studies produced by the social leaders at these brands: ARM by Kerry McGuire Balanza, Director of Strategic Marketing; Aviva by Jan Gooding, Global Brand Director; Dell by Stuart Handley, Communications Director; Evans Cycles by Will Lockie, Head of Social Media; GlaxoSmithKlein (Ribena) by Verity Clifton, Brand Marketing Manager; Kodak by Madlen Nicolaus, Social Media Manager; Phillips by Hans Notenboom, Global Director B2B Online; Sage by Cath Sheldon, Online PR Specialist. There is more, connect with the co-authors and other readers by joining The Social Media MBA Alumi group, visit http://www.socialmedia-mba.com or search or the group on LinkedIn to stay updated on the latest, ask questions or join the discussions"-- Provided by publisher.
Machine generated contents note: Preface 5 Part I. Foundation 8 1. Quick Recap 9 2. Bridging The Social Media Gap 18 Part II. Strategy Development 28 3. Inspiring And Facilitating Creativity 29 4. The Rise Of Branded Content 36 5. Power Of Integration 44 6. Intent Is The New Demographic 55 7. Targeting The Easily Influenced Not The Highly Influential 64 Part III. Strategy Delivery 74 8. Your Best Advocates 75 9. The Profit Manifesto 83 10. Social Media Business Engineering 94 11. Power Struggles Of The Advocate Age 105 Part IV. Case Studies 116 12. ARM 117 13. Aviva 120 14. Dell 123 15. Evans Cycles 126 16. GlaxoSmithKlein 129 17. Kodak 132 18. Phillips 136 19. Sage 139 Part V. Future 143 20. The Ethnocentric Bias 144 21. One Digital Dragons, Elephants and Tigers 153 22. Design Thinking and Social Media 164 23. God Technology 173 Conclusion 180 Biographies 182 .
Includes index.
Jason Baguia (Recommending Faculty) : Arts and Humanities Cluster
Keywords: Information technology -- Management; Social media; Customer relations; Internet marketing; Branding (Marketing); SOCIAL SCIENCE / Media Studies